TRADITIONAL AND INNOVATIVE MEANS OF EFFECTIVE FORMATION OF ICT COMPETENCE OF SOCIAL WORKERS - Blyznyuk, Tetyana; Lemko, Halyna; Blyznyuk, Oleksandr; Fomin, Sergiy (Mountain School of Ukrainian Carpaty, 2023)
Information and communication competence contributes to the general development of social workers as high-quality specialists, but also to their professional activity and interaction with the target audience. The article reveals the essence and structural components of ICT competence of future specialists in the social sphere. It is noted that information and communication competence is necessary for the professional growth of a specialist, a representative of a modern digital society, and urgent for activation of communication between participants in the field of social services during wartime and other current challenges. The traditional and innovative means of forming the ICT competence of future social workers during the study of the Foreign Language of Professional Communication course were analyzed. In particular, efficiency and expediency of using interactive tasks, digital mobile applications, tools and online resources for this purpose is justified. The researchers emphasized in the paper the importance of digital interaction, which is implemented in the process of educational tasks presented in the article, as well as the effectiveness of working with authentic texts that introduce ways to solve such a problem in the world experience. The specifics of the use of digital tools as means of forming the information and communication competence of future social workers in the educational space are characterized (tools for creating and viewing videos, multimedia presentations, slide shows, search engines, Google forms, services for the introduction of distance and blended learning, polls, assessment, etc.).